Reconstructing Civic Education in the Context of National Identity and Cultural Pluralism: A Conceptual Study - Afriadi, Bambang; Fitri, Fitri (PT. BATARI EDU CALYA, 2025)
This article discusses efforts to reconstruct civic education within the multicultural, democratic, and dynamic context of Indonesia. Using a qualitative approach with a literature study method, this study traces the development of citizenship concepts from a legal-formal dimension toward a paradigm of active, critical, and transformative citizenship. The research analyzes various theories of citizenship, character education, and multiculturalism relevant to the reform needs of civic education in the global era. The findings indicate that civic education in Indonesia needs to be reconstructed from an indoctrination model to a reflective and contextual learning model. This process includes strengthening Pancasila values, fostering critical awareness, developing global citizenship competencies, and managing cultural pluralism inclusively. Thus, civic education can serve as a strategic vehicle in shaping intelligent, democratic, tolerant citizens who care about national and humanitarian life.